Optimization of antioxidant activity and characterization of probiotic cascara beverage fermented using water kefir grain [Optimasi aktivitas antioksidan dan karakterisasi minuman probiotik cascara hasil fermentasi menggunakan bibit kefir air] - Putri, Destiana Adinda; Nalurita, Indah; Heldiyanti, Rina; Zulkarnaen, Zulkarnaen (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2024)
Cascara is a beverage derived from dried coffee cherry pulp, known to have good functional value but with a short shelf life. Fermentation is a technique that can enhance cascara beverages' shelf life and quality and their functional value due to the presence of probiotics and increased antioxidant compounds. The study aimed to optimize the fermentation conditions of cascara tea with water kefir seeds to improve the microbiota content of Lactobacillus sp, Bifidobacterium sp, and Saccharomyces cerevisiae and the antioxidant activity of the beverage. The method in this study used Response Surface Methodology (RSM) with a design selection of Central Composite Design (CCD), using two independent variables, namely fermentation time (X1) and Grain Concentration (X2), with a response of antioxidant activity (%). The findings indicated that a fermentation period of 48 hours and a grain concentration of 8.58% resulted in a probiotic drink exhibiting the maximum antioxidant activity of 65.53%. This optimum treatment resulted in a drink with IC50 antioxidant activity of 173.66 ppm, total phenol 477.24 mg GAE/mL, brightness value (L*) 30.69, redness (a*) 14.06, yellowness (b*) 29.57, pH 3.57, TPT 8.80 (ᵒBrix), viscosity 1.62 mPa.s, total LAB 8.54 log CFU/ml, and total yeast & mold 10.93 log CFU/ml.